Palaeo-Eskimo genetic ancestry and the peopling of Chukotka and North America - Flegontov, Pavel; Ezgi Altinisik, N.; Changmai, Piya; Rohland, Nadin; Mallick, Swapan; Adamski, Nicole; A. Bolnick, Deborah; Broomandkhoshbacht, Nasreen; Candilio, Francesca; J. Culleton, Brendan; Flegontova, Olga; Max Friesen, T.; et al. (Online Ancient Genome Repository, 2019)
Much of the American Arctic was first settled 5,000 years ago, by groups of people known as Palaeo-Eskimos. They were subsequently joined and largely displaced around 1,000 years ago by ancestors of the present-day Inuit and Yupik. The genetic relationship between Palaeo-Eskimos and Native American, Inuit, Yup’ik and Aleut populations remains uncertain. Here we present genomic data for 48 ancient individuals from Chukotka, East Siberia, the Aleutian Islands, Alaska, and the Canadian Arctic. We co-analyse these data with data from present-day Alaskan Inupiat and West Siberian populations and published genomes. Using methods based on rare-allele and haplotype sharing, as well as established techniques, we show that Palaeo-Eskimo-related ancestry is ubiquitous among people who speak Na-Dene and Eskimo–Aleut languages. We develop a comprehensive model for the Holocene peopling events of Chukotka and North America, and show that Na-Dene-speaking peoples, people of the Aleutian Islands, and Yupik and Inuit across the Arctic region all share ancestry from a single Palaeo-Eskimo-related Siberian source.